Association between pre-operative biological phenotypes and postoperative pulmonary complications: An unbiased cluster analysis. Issue 9 (September 2018) - Serpa Neto, Ary; Bos, Lieuwe D.; Campos, Pedro P.Z.A.; Hemmes, Sabrine N.T.; Bluth, Thomas; Calfee, Carolyn S.; Ferner, Marion; Güldner, Andreas; Hollmann, Markus W.; India, Inmaculada; Kiss, Thomas; Laufenberg-Feldmann, Rita; et al.
Abstract : BACKGROUND: Biological phenotypes have been identified within several heterogeneous pulmonary diseases, with potential therapeutic consequences. OBJECTIVE: To assess whether distinct biological phenotypes exist within surgical patients, and whether development of postoperative pulmonary complications (PPCs) and subsequent dependence of intra-operative positive end-expiratory pressure (PEEP) differ between such phenotypes. SETTING: Operating rooms of six hospitals in Europe and USA. DESIGN: Secondary analysis of the 'PROtective Ventilation with HIgh or LOw PEEP' trial. PATIENTS: Adult patients scheduled for abdominal surgery who are at risk of PPCs. INTERVENTIONS: Measurement of pre-operative concentrations of seven plasma biomarkers associated with inflammation and lung injury. MAIN OUTCOME MEASURES: We applied unbiased cluster analysis to identify biological phenotypes. We then compared the proportion of patients developing PPCs within each phenotype, and associations between intra-operative PEEP levels and development of PPCs among phenotypes. RESULTS: In total, 242 patients were included. Unbiased cluster analysis clustered the patients within two biological phenotypes. Patients with phenotype 1 had lower plasma concentrations of TNF-α (3.8 [2.4 to 5.9] vs. 10.2 [8.0 to 12.1] pg ml −1 ; P < 0.001), IL-6 (2.3 [1.5 to 4.0] vs. 4.0 [2.9 to 6.5] pg ml −1 ; P < 0.001) and IL-8 (4.7 [3.1 to 8.1] vs. 8.1 [6.0 to 13.9] pg ml −1 ; P < 0.001). Phenotype 2 patients had the highest incidence of PPC (69.8 vs. 34.2% in type 1; P < 0.001). There was no interaction between phenotype and PEEP level for the development of PPCs (43.2% in high PEEP vs. 25.6% in low PEEP in phenotype 1, and 73.6% in high PEEP and 65.7% in low PEEP in phenotype 2; P for interaction = 0.503). CONCLUSION: Patients at risk of PPCs and undergoing open abdominal surgery can be clustered based on pre-operative plasma biomarker concentrations. The two identified phenotypes have different incidences of PPCs. Biologic phenotyping could be useful in future randomised controlled trials of intra-operative ventilation. TRIAL REGISTRATION: The PROtective Ventilation with HIgh or LOw PEEP trial, including the substudy from which data were used for the present analysis, was registered at ClinicalTrials.gov (NCT01441791). Abstract : Supplemental Digital Content is available in the text